Reconstruction of STEM-Based Learning Videos on Topics of Escherichia Coli Bacteria - Ino Angga Putra; Yati Ludiana; Anggun Wulandari (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The purpose of this development research is to determine the design and feasibility of STEM-based learning videos on Escherichia coli bacteria material. The type of research used is research and development (R & D) with a 4D development model. However, in this study, it was limited to 3D without the Dessiminase stage. The research subjects were students of the 6th semester biology education study program with a total of 7-10 students. The data used are quantitative data (validation questionnaire scores and student responses) and qualitative data (suggestions and comments from validators and students). Data retrieval using a material and media validation questionnaire instrument and student response questionnaires. The results obtained are the formation of a product in the form of STEM-Based Learning Videos on Escherichia coli Bacteria with the